2016
DOI: 10.1186/s12891-016-1167-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bisphosphonate therapy on bone geometry, volumetric bone density and bone strength of femoral shaft in postmenopausal women with rheumatoid arthritis

Abstract: BackgroundThere is evidence that postmenopausal women with rheumatoid arthritis (RA) on glucocorticoid (GC) therapy and bisphosphonate (BP) have an increased risk for atypical subtrochanteric and atypical diaphyseal femoral fracture (AFF). The underlying mechanism has not been elucidated so far. Using peripheral quantitative computed tomography (pQCT), the aim of the present study was to compare bone geometry, volumetric bone mineral density (vBMD) and bone strength of femoral shaft in BP-treated and BP-naïve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In this study, we demonstrated that treatment with ZOL alone has little effect on RA-derived secondary osteoporosis, but that when it is combined with MTX it reduces both RA inflammation and bone destruction. Previous studies have shown that for women with postmenopausal RA, whose femoral bone density is correlated with the cross-sectional area of the proximal thigh muscle and the time since menopause, bisphosphonate treatment alone has no significant effect on the bone density of the femoral shaft [13]. On the contrary, in other studies from women with postmenopausal RA and a history of corticosteroid treatment, DAS28 score and bone density of the lumbar spine and femoral neck were significantly improved after 12 months of treatment with alendronate or risedronate along with the original RA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated that treatment with ZOL alone has little effect on RA-derived secondary osteoporosis, but that when it is combined with MTX it reduces both RA inflammation and bone destruction. Previous studies have shown that for women with postmenopausal RA, whose femoral bone density is correlated with the cross-sectional area of the proximal thigh muscle and the time since menopause, bisphosphonate treatment alone has no significant effect on the bone density of the femoral shaft [13]. On the contrary, in other studies from women with postmenopausal RA and a history of corticosteroid treatment, DAS28 score and bone density of the lumbar spine and femoral neck were significantly improved after 12 months of treatment with alendronate or risedronate along with the original RA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs have been shown to inhibit bone resorption of osteoclasts, reduce bone turnover rate, increase bone strength, protect articular cartilage, and have anti-inflammatory effects [10]. These therapeutic effects have been demonstrated in senile and postmenopausal osteoporosis, but results from studies of RA-associated osteoporosis are inconclusive [12, 13]. In this study, we aimed to determine the efficacy of ZOL alone or in combination with MTX for the prevention and treatment of bone destruction in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…A heated debate has recently arisen on the long-term consequences of their effects on bones [29]. Moreover, Bisphosphonate-associated osteopetrosis once reported by Whyte et al [30] may be nothing more than a coincidence, given the significant enhancement of bone mineral density shown by other authors [31][32][33]. However, between 2005 and 2010 alone, WHO counted more than 800 fragility fracture reports that could have been related to Bisphosphonates therapy [34][35][36].…”
Section: Discussionmentioning
confidence: 99%